Fraud Analysis on Illegal Online Lending Using Habermas' Theory of the Public Sphere - Shonhadji, Nanang (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
This study aims to investigate and expose the fraudulent practices conducted by P2P lending service providers in illegal online loan schemes, through the lens of Habermas' critical theory. The research was conducted in areas affected by illegal online lending practices, with informants consisting of users and victims of fraud from Surabaya, Sidoarjo, and Pasuruan, East Java. This qualitative study adopts a Radical Humanist Paradigm approach. The findings indicate that Habermas' theory of the public sphere provides a useful framework for understanding the mechanisms of fraud employed by illegal financial technology lenders. The study underscores the need for clearer regulations governing P2P lending transactions conducted via online platforms, as well as stricter sanctions for perpetrators of illegal online loan fraud, as part of raising public awareness and ensuring consumer protection. Keywords: fraud, online loans, Habermas